2019
DOI: 10.3766/jaaa.17012
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Cochlear Implant Listeners’ Ability to Perceive Minimal Audible Angle Differences

Abstract: Background: Bilateral inputs should ideally improve sound localization and speech understanding in noise. However, for many bimodal listeners [i.e., individuals using a cochlear implant (CI) with a contralateral hearing aid (HA)], such bilateral benefits are at best, inconsistent. The degree to which clinically-available HA and CI devices can function together to preserve interaural time and level differences (ITDs and ILDs, respectively) enough to support the localization of sound sources is a question with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Beijen et al [2010] tested children with a CI on one side and a hearing aid on the other side with a left-right discrimination task and showed that the children performed significantly better than chance. Zaleski-King et al [2019] tested MAA via headphones in adult participants with a CI on one side and a hearing aid on the other side and found similar results. Bilaterally provided CI participants benefit from the second CI: Senn et al [2005] showed that the participants performed better in the MAA task with two CI than with one CI.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Beijen et al [2010] tested children with a CI on one side and a hearing aid on the other side with a left-right discrimination task and showed that the children performed significantly better than chance. Zaleski-King et al [2019] tested MAA via headphones in adult participants with a CI on one side and a hearing aid on the other side and found similar results. Bilaterally provided CI participants benefit from the second CI: Senn et al [2005] showed that the participants performed better in the MAA task with two CI than with one CI.…”
Section: Introductionmentioning
confidence: 74%
“…In contrast, hearing-impaired children tested without their hearing aids did not consistently benefit from frontal positions of the sound sources in the MAA task [Meuret et al, 2017]. Zaleski-King et al [2019] measured MAA via headphones in bimodally fitted adults and showed no increasing MAA with increasing laterality. Most of the participants of the present study also gained no benefit from frontal signal presentation.…”
Section: Dependence On Lateralitymentioning
confidence: 90%
“…In both studies, the temporal matching of both sides resulted in improved localization accuracy. Another study found no benefit in sound localization by matching the CI to the hearing aid delay [ 2 ]. In our study no significant correlation was found between JND-ILD and sound localization errors.…”
Section: Discussionmentioning
confidence: 99%
“…The speakers spanned an angle of −90° left to +90° right with a spacing of 30°. Since more sound source directions could increase the test duration and thus cause the subject fatigue, only five of seven loudspeakers (all speakers were real and available) were used for sound presentation in this experiment ( Godar and Litovsky, 2010 ; Zaleski-King et al, 2019 ). A schematic diagram of the loudspeaker arrangement is shown in Figure 1E .…”
Section: Methodsmentioning
confidence: 99%